1979
DOI: 10.1172/jci109338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytochalasin B and D on Groups of Insulin Receptors and on Insulin Action in Rat Adipocytes

Abstract: A B S T R A C T The possible physiological imiiportainee of the groups of insulin receptors on rat adipocytes and the relationship of these groups to insulin action were investigated. The effect of cytochalasin B aind D on l)iological actions of insulin was measured aind coimipared with the effect of these agents on the ultrastructural distribution of groups of insulin receptors. Cytochalasin B had no effect on epinephrine-stimulated lipolysis, insulin inhibition of epinephrine-stimulated lipolysis, or insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
20
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 41 publications
8
20
0
Order By: Relevance
“…Several reports also suggest that the internalization process may be of little significance in mediating insulin action in adipose tissue. For example, Jarett and Smith (25) did not find coated pits on adipocyte plasma membranes when assayed by electron microscopy, and have also reported that clustering of receptors in fat cells is not related to biologic response (26). Taken together with our data, these studies suggest that tissue-specific differences may exist for potentiation of insulin action by sulfonylureas.…”
Section: Resultssupporting
confidence: 67%
“…Several reports also suggest that the internalization process may be of little significance in mediating insulin action in adipose tissue. For example, Jarett and Smith (25) did not find coated pits on adipocyte plasma membranes when assayed by electron microscopy, and have also reported that clustering of receptors in fat cells is not related to biologic response (26). Taken together with our data, these studies suggest that tissue-specific differences may exist for potentiation of insulin action by sulfonylureas.…”
Section: Resultssupporting
confidence: 67%
“…In contrast, the organizational pattern found on liver plasma membranes showed that the receptors occurred predominantly as single receptor sites (3). Cytochalasin B, but not cytochalasin D, was found to partially disrupt the groups of receptors on adipocytes as determined by both visual and computer-assisted analytical methods (2,4). These findings indicated that neither microfilaments nor actin is involved in maintaining the grouped receptors and suggested that cytochalasin B, due to its thiol binding properties (5), may prevent the formation of disulfide bonds that, in part, hold together the groups of insulin receptors.…”
mentioning
confidence: 78%
“…Morphological studies of the distribution of insulin receptors on rat adipocyte plasma membranes using monomeric ferritininsulin have shown that the occupied insulin receptors occurred predominantly in natural groups of two to six receptors (1,2). In contrast, the organizational pattern found on liver plasma membranes showed that the receptors occurred predominantly as single receptor sites (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adipocytes were prepared from epididymal fat pads of 120-g Sprague-Dawley rats by collagenase digestion as described (16 (21). Fm-I, like 125I-insulin, will identify only occupied receptor sites and, in the event that the label, the hormone, or the receptor is degraded, the localization of the label relative to the hormone receptor is unknown.…”
Section: Methodsmentioning
confidence: 99%